2021
DOI: 10.3390/ijerph18189910
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Parameters in Patients with Diabetes Mellitus and in the General Adult Population—Trends over Five Years: Results of the Austrian National Health Interview Series

Abstract: Background: Not smoking, performing >150 min of aerobic physical activity (PA) and muscle strengthening exercises/week, and consuming >5 portions of fruit and vegetables/day are lifestyle recommendations for both the general population and people with diabetes mellitus (DM). Methods: A total of 15,771 and 15,461 persons from the Austrian Health Interview Surveys 2014 and 2019, respectively, including 4.9% and 6.0% of people with DM, were analysed in terms of their smoking, PA, and nutritional behaviours.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…41 Along this line, a study by Bennie et al 23 in ~1.7 million US adults found that meeting both aerobic and MSA guidelines was associated with a lower prevalence of obesity, and associations were stronger for higher obesity classes. Similar differences in adherence to physical activity guidelines have been reported in other countries, including Austria, 30 Australia, 21 Finland, 22 Germany, 25 The Netherlands 31 and South Korea, 33 36 indicating that these Our study provides an accurate estimate of prevalence of physical activity at the population level, which is an important modifiable chronic disease risk factor. 10 11 The importance of meeting both guidelines from a clinical perspective has previously been highlighted in some studies included in the present meta-analysis.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…41 Along this line, a study by Bennie et al 23 in ~1.7 million US adults found that meeting both aerobic and MSA guidelines was associated with a lower prevalence of obesity, and associations were stronger for higher obesity classes. Similar differences in adherence to physical activity guidelines have been reported in other countries, including Austria, 30 Australia, 21 Finland, 22 Germany, 25 The Netherlands 31 and South Korea, 33 36 indicating that these Our study provides an accurate estimate of prevalence of physical activity at the population level, which is an important modifiable chronic disease risk factor. 10 11 The importance of meeting both guidelines from a clinical perspective has previously been highlighted in some studies included in the present meta-analysis.…”
Section: Discussionsupporting
confidence: 75%
“…After removing duplicates and screening titles, 67 studies were assessed for eligibility based on full text. A total of 21 studies were finally included in the present meta-analysis 8 9 21–39. The PRISMA flow diagram illustrating the number of studies excluded at each stage of the systematic review and meta-analysis is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Smoking, high-risk drinking, and lack of physical activity are risk factors for poor health, but improving them can prevent or delay the worsening of chronic diseases [ 2 ]. Engaging in multiple risky behaviors is associated with a greater risk of chronic disease and mortality as compared with engaging in one or no risk behaviors [ 3 , 4 , 5 ]. In addition, mortality risk and the risk of poor health-related quality of life increase when the number of poor behaviors increases [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%